Barriers to the conduct and application of research among complementary and alternative medicine professions in Australia and New Zealand: A cross-sectional survey. (August 2021) - Veziari, Yasamin; Kumar, Saravana; Leach, Matthew
Highlights: CAM stakeholders continue to face barriers when engaging with research. Multi-factorial barriers exist across the continuum of evidence-based practice. While some are universal barriers to engaging with research, some are CAM-centric. Addressing these barriers will require a comprehensive long-term strategy. Abstract: Introduction: Despite the growing international popularity and use of complementary and alternative medicine (CAM), the uptake of evidence-based practice (EBP) in CAM has been slow. This cross-sectional survey aimed to further our understanding of the factors impacting EBP uptake in CAM. Methods: The 32-item oBSTACLES instrument was administered online using the SurveyMonkey™platform. The survey evaluated barriers to both the conduct and application of research among CAM practitioners and researchers, from multiple CAM disciplines across Australia and New Zealand. Participants were recruited via practice-based research networks, professional associations, CAM educational institutions, CAM research centres, pertinent product manufacturers and social media platforms. Data were analysed using descriptive statistics. Results: Six hundred and eighty-two CAM stakeholders responded to the survey. Barrier items were divided into two interlinked constructs, "capacity" and "culture". Capacity related to issues regarding access, competency, bias, incentives, and time, whereas culture related to values and complex systems. Under capacity, the greatest proportion of participants (>70 %) agreed that access was a barrier to the conduct and application of research, including lack of funding, institutional support, research training and collaborations. In terms of culture, the majority of participants (>60 %) agreed that values were a barrier to research conduct and application, including limited undergraduate research opportunities and diverse views of evidence. Conclusion: Findings from this research suggest a multitude of barriers negatively impact the conduct and application of research in CAM. Insights gained from this research will be instrumental in developing actionable strategies aimed at mitigating the impact of these barriers to improve research engagement in CAM.